Changes in Corneal Biomechanics and Glaucomatous Visual Field Loss. Issue 5 (May 2021) - Chan, Eric; Yeh, Kaileen; Moghimi, Sasan; Proudfoot, James; Liu, Xiongfei; Zangwill, Linda; Weinreb, Robert N.
Abstract : Precis: A lower baseline corneal hysteresis and a decrease in corneal resistance factor (CRF) over time are associated with higher risk of visual field progression in glaucomatous and glaucoma suspect eyes. Purpose: The aim was to investigate the longitudinal change in CRF and cornea hysteresis (CH) as risk factors for visual field progression. Materials and Methods: In this prospective observational cohort study, 72 eyes of 48 glaucoma or glaucoma suspect patients were followed for an average of 4.5 years. Baseline and follow-up CH and CRF measurements were performed with the Ocular Response Analyzer (Reichert Ophthalmic Instruments Inc., Depew, N.Y.). Evaluation of rates of visual field change during follow-up was performed using visual field mean deviation. Univariable and multivariable linear mixed models assessed the relationship of visual field progression with baseline CRF and CH as well as with changes in CRF and CH. Results: The mean baseline CH was 9.0 (95% confidence interval: 8.6-9.4) mm Hg and the mean baseline CRF was 9.3 (95% confidence interval: 8.8-9.9) mm Hg. There was no statistically significant difference in average CH and CRF measurements over time. In multivariable modeling adjusting for age, race, and mean intraocular pressure during follow-up, each 1 mm Hg lower in baseline CH and 1 mm Hg decrease in CRF over time were associated with a 0.12 ( P =0.042) and 0.14 dB/year ( P =0.007) faster rate of visual field mean deviation loss, respectively. Similar findings were found in glaucoma eyes but not found in glaucoma suspect eyes. Conclusion: Visual field progression was associated with a lower baseline CH and a decrease in CRF over time. Assessment of corneal resistance and elasticity at baseline and during follow-up examinations should be considered to identify those eyes at highest risk of visual field progression. Abstract : Supplemental Digital Content is available in the text.